The Effect of Compensation and Motivation on Employee Performance Through the Mediation of Job Satisfaction (Case Study on Savings and Loan Cooperatives in Karangasem Regency) - Pande Nyoman Santi Ardani; Ida Ayu Putu Widani Sugianingrat; Mirah Ayu Putri Trarintya (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to determine the effect of compensation on employee performance , determine the effect of motivation on employee performance , determine the effect of work compensation on job satisfaction , determine the effect of work motivation on employee job satisfaction , knowing the effect of job satisfaction on employee performance , knowing the effect of compensation on employee performance through the mediation of job satisfaction , and knowing the effect of motivation on employee performance through mediating job satisfaction at KSP in Karangasem Regency . Using a quantitative approach. Questionnaires that have been tested for validity and reliability are then analyzed using descriptive analysis and inferential analysis with Structural Equation Model-Partial Least Square analysis and produce results.